ダイ19ジ ナンキョク チイキ カンソク ナツタイ 1977-1978 ホウコク - 大瀬, 正美; オオセ, マサミ; OSE, Masami (国立極地研究所, 1979)
P(論文) 第19次南極地域観測隊の観測計画および夏期行動計画の概要を述べる.平沢隊長以下隊員40名,4名のオブザーバー(NHK取材班3名,チリーからの交換科学者1名および約500トンの物資を積載した「ふじ」は1977年11月25日東京港を出発,147日間の全行程を終え,1978年4月20日東京港に帰った.「ふじ」は12月28日氷縁に着き,1月17日には8年ぶりに昭和基地に接岸した.1月24日までに全越冬物資を昭和基地に運んだ. Summer operations of the 19th Japanese Antarctic Research EX-pedition (JARE-19) are outlined, with a brief description of the summer activities. The icebreaker FUJI, carrying 500 tons of cargo and equipped with three helicopters, left Tokyo on November 25, 1977. The expedition led by Prof. T. HIRASAWA of the National Institute of Polar Research consisted of 40 members, ten of which constituted the summer party led by the author, deputy leader of the exnedition. Three press men joined the summer party. Dr. AlbertoJ. FOPPIANO, an exchange scientist from Chile, accompanied the summer party from Fremantle of Australia to Port Louis, Mauritius. After leaving Fremantle on December 16,1977, the FUJI reached the edge of fast ice, about 250 km east-northeast of Syowa Station, on December 30, 1977. The field party of six persons (three geologists, one geophysicist, one surveyor and one biologist) camped at Cape Ryugu 220 km east-northeast of Syowa Station from December 30,1977 to January 14,1978. The FUJI anchored at Syowa Station from January 17 to February 3,1978. Five other field surveys of geoscience and biology were successfully carried out in the snow-free areas along the coast of Liitzow-Holm Bay from January 24 to February 3, 1978. A return trip to the inland Mizuho Station was also accomplished. Two sounding rockets of S-210 were successfully launched on January 28 and February 6,1978. The FUJI returned to Tokyo on April 20,via Port Louis of Mauritius and Singapore. departmental bulletin paper